Effect of different floor types on body weight of Surti goats under asbestos roofed house (Indian Journal of Animal Production and Management, 2024)
The present study was conducted to compare the effect of different floor types on body weight of Surti goats under asbestos roofed house during winter, hot dry and hot humid season. Twenty seven adult dry non pregnant (20 - 30 Kg) farm born Surti goats were divided randomly on body weight basis in three treatment groups i.e. T1: Earthen (Kachcha), T2: Brick and T3: Cement concrete (Pucca) floor. Each treatment groups comprised of three replications and each having three animals. The experimental animals were maintained on ICAR feeding standard (2013) and Total Mixed Ration (TMR) offered daily in morning and afternoon in groups. The body weight (Kg) of experimental animals was comparable among treatment groups. However, the body weight was significantly (p < 0.05) higher in summer (27.78 ± 0.27) and hot humid (28.02 ± 0.27) seasons as compared to winter (24.30 ± 0.30) season, respectively. The results indicated that the floor type did not influence body weight of adult goats reared under asbestos roofed house.
Keywords: Floor; Body weight; Asbestos roof